Pengaruh Profitabilitas dan Nilai Perusahaan Terhadap Agresivitas Pajak pada Perusahaan Manufaktur ASEAN - Erlin Dania Rosmalinda (Yayasan Literasi Ilmiah Indonesia, 2024)
Purpose: This study aims to examine the influence of profitability and firm value on tax aggressiveness among manufacturing companies listed on the ASEAN stock exchange from 2018 to 2023. Method: A quantitative research method is employed, using a sample of manufacturing companies listed on the ASEAN stock exchange. Finding: The results of the study indicate that profitability as measured by Return on Assets (ROA) has a positive impact on tax aggressiveness. This means that companies with high ROA, the higher the level of profit obtained by the company, the higher the tax burden, so the company will be more aggressive towards taxes. While the company value has no effect on tax aggressiveness. This research provides a contribution to further testing to determine what indicators influence tax aggressiveness in a company so that tax aggressiveness can be minimized. Novelty: Various differences in previous research and research phenomena, the topic of tax aggressiveness is still interesting to be reexamined because in ASEAN cases of tax aggressiveness are still high compared to other parts of Asia. With this research, it will be a consideration for the company what the company will do to overcome this case. So that in the future the company hopes to be more orderly in terms of taxation.